Prostaglandin E(2)-EP4 signaling suppresses adipocyte differentiation in mouse embryonic fibroblasts via an autocrine mechanism - Inazumi, Tomoaki (The American Society for Biochemistry and Molecular Biology, 2011)
The prostaglandin (PG) receptors EP4 and FP have the potential to exert negative effects on adipogenesis, but the exact contribution of endogenous PG-driven receptor signaling to this process is not fully understood. In this study, we employed an adipocyte differentiation system from mouse embryonic fibroblasts (MEF) and compared the effects of each PG receptor-deficiency on adipocyte differentiation. In wild-type (WT) MEF cells, inhibition of endogenous PG synthesis by indomethacin augmented the differentiation, whereas exogenous PGE(2), as well as an FP agonist, reversed the effect of indomethacin. In EP4-deficient cells, basal differentiation was upregulated to the levels in indomethacin-treated WT cells, and indomethacin did not further enhance differentiation. Differentiation in FP-deficient cells was equivalent to WT and was still sensitive to indomethacin. PGE(2) or indomethacin treatment of WT MEF cells for the first two days was enough to suppress or enhance transcription of the Pparg2 gene as well as the subsequent differentiation, respectively. Differentiation stimuli induced COX-2 gene and protein expression, as well as PGE(2) production, in WT MEF cells. These results suggest that PGE(2)-EP4 signaling suppresses adipocyte differentiation by affecting Pparg2 expression in an autocrine manner and that FP-mediated inhibition is not directly involved in adipocyte differentiation in the MEF system.